+0  
 
0
118
1
avatar+50 

 (x^2-4x-12)/(x^2-25)≥0

Bobbly  May 28, 2018
edited by Bobbly  May 30, 2018
edited by Bobbly  May 30, 2018
 #1
avatar+945 
+4

Hey bobbly!

 

 \(\frac5{x+3}+\frac{3}{x-2}=4\\ \frac{5\cdot(x-2)+3\cdot(x+3)}{(x-2)(x+3)}=4\\ \frac{5x-10+3x+9}{x^2+x-6}=4\\ 5x-10+3x+9=4x^2+4x-24\\ 4x^2-4x-23=0\)

 

We then use the quadratic formula: \(x = {-b \pm \sqrt{b^2-4ac} \over 2a} \), to solve for x. 

 

\(x_1=\frac{-\left(-4\right)+\sqrt{\left(-4\right)^2-4\cdot \:4\left(-23\right)}}{2\cdot \:4}=\frac{1+2\sqrt{6}}{2}\)

\(x_2=\frac{-\left(-4\right)-\sqrt{\left(-4\right)^2-4\cdot \:4\left(-23\right)}}{2\cdot \:4}=\frac{1-2\sqrt{6}}{2}\)

 

I hope this helped,

 

Gavin

GYanggg  May 28, 2018

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.